Changes in the area of urban green space in cities of western Poland - Krzyżaniak, Michał; Świerk, Dariusz; Szczepańska, Magdalena; Urbański, Piotr (Bulletin of Geography. Socio-economic Series, 2018)
Extensive and continuous areas of urban greenery are essential for the proper functioning of cities and for achieving optimal natural conditions. The aim of our study was to investigate the changes in the areas of public green space of Szczecin, Poznań and Wrocław in the years 1996-2013, and compare data on public greenery with demographic data and changes in the spatial development of the described cities. We used a linear regression and exponential regression to explain the results. In our opinion, it is necessary to establish the appropriate proportion of public greenery to the built-up areas in cities. Otherwise, we will be observing an adverse reduction of green areas in relation to residential areas. Surveys also indicate the need for action to prevent the outflow of population to the suburban areas.